Hydrodynamic assessment of a semi-submersible aquaculture platform in uniform fluid environment. (1st October 2021) - Liu, Hang-Fei; Bi, Chun-Wei; Xu, Zhijing; Zhao, Yun-Peng
Abstract: Predicting the distribution of flow velocity inside a semi-submersible aquaculture platform and taking measures to optimize the flow field are critical to provide a dependable inhabit for farmed fish. This paper examines the hydrodynamics of a semi-submersible fish farm under current using the porous media method combined with a rigid wall based on the shear stress transport k-omega turbulence model. The results show that the presence of nets expands the low flow area and provides a better inhibit for farmed fish in the severe currents. The increase of net solidity enhances the damping effect on the flow, and it also simultaneously increases the current loads acting on the net. The attenuation caused by different net solidities produces a 66.10 % deficit of the flow velocity in maximum inside aquaculture platform. A maximum increase of 36.82 % for the drag force acting on the aquaculture platform is obtained. Furthermore, the distribution of drag force acting on the aquaculture platform in current is also assessed. Although the drag force of the frame-only is approximately twice compared to the net-only case, the improvement in the strength of the net structure under the action of flow should not be ignored. Highlights: A novel dependable habitat of farmed fish: a semi-submersible aquaculture platform is researched. A new method combining the porous media and rigid wall is applied to analyze hydrodynamic characteristic. The influence of the existence of the net and the net solidity on the flow field and drag force is studied. The drag force acting on the net-only and frame-only for the aquaculture platform are discussed.